La unión de hecho, debe considerarse como estado civil en el código civil Ecuatoriano, en la ley de registro civil e identificación y cedulación, por lo tanto es necesario reformar los mencionados cuerpos legales, estableciendo a la unión de hecho como un nuevo estado civil de las personas. - Medardo Hoyos, Ángel (2012)
The topic that I have intended to develop, is in fact related with the lack of recognition of the Union as a civil new state of people; at the present time this relationship is only recognized as an element that generates rights and obligations but I don't eat or civil new state recognized by the corresponding law. He/she understands each other for civil state the particular condition that characterizes a person in that he/she makes to their personal bonds with individuals of another sex and the civil state exists from the moment in that the human being believes the marriage's institution, but the same one is linked specifically with the reach that has the State as political institution to organize and to govern the establishment of bonds of this type. It is very important that in the social life of people that you/they maintain relationship denominated sentimental union in fact of which you/they have formed a family and it is not grateful legally as a civil new state and that it is effective in our society that historically I can affirm that it is as old as the same humanity, because the first relationship of coexistence that the human being has had was, the civil other states that today knows them and that they are accepted by the society they are later that they have been given of agreement as the society he/she has left civilizing. In the current moments, it would be reason of reflection of the authorities who you/they have the arduous task of to create and to modify the laws, recognizing this relationship like a civil new state because in the country, most of people of the coast, the natives live this relationship in fact, in the mountain and also the other regions of the country the mestizos are married and therefore they have a civil grateful state before the law. As it is of general knowledge they exist different types of civil state that they vary according to the type of relationships that a person maintains with other; among the most common we find the one of single (those people that are not committed legally with others), the one of having married (those that yes he are) in of divorced (people that have broken up the loving or legal bond with their couples) the widowers (those that have lost their couple for deceso). It is my opinion that the civil state is the artificial position that a person occupies in society in front of the other ones trusting him/her the way of being and civil condition, what allows to sum up the person's artificial identity, also constitutes an artificial situation that the person has in the society in relation to her family relationships in that you/he/she imposes him/her certain obligations and you/he/she confers him/her certain civil rights; being considers this way that the civil state is a class inside the variety of civil existent states in reason that the person's position in the community and the relationships with its fellow men. Therefore the civil state is properly a right, it is essentially the person's attribute, a quality that takes gets that it allows him/her to differ and to be distinguished legally of the other ones. A fellow can go altering his states depending on the facts or juridical acts that influence in the person what you/they transcend in the civil state a family that although it is certain it is recognized in the Civil Code, but that it is not registered in the Civil Registration, he doesn't have social, better recognition it minimizes them to him or they are given the name of concubinos, not well alive, etc. We should understand that the relationship of union in fact, legally it establishes rights as for the goods the Civil Code, it determines that he/she is formed the society of goods and obligations between two people and their descendant, for what should be recognized by the Law of Civil Registration, Identification and Cedulación, as a new state of people.